The pattern of the frailty syndrome in chronic heart failure - Snejana B. Vetrila; Livi T. Grib; Anastasia A. Ivanes (Romanian Journal of Medical Practice, 2023)
Introduction. The coexistence of cardiovascular diseases and frailty has been demonstrated, with the prevalence of frailty ranging from 19% to 76%. The presence of frailty significantly influences decision making regarding the type and timing of diagnostic strategies. Objectives. To assess the features of frailty syndrome in patients with heart failure. Material and methods. A comprehensive search was conducted in PubMed, Google Search, and ResearchGate databases using the keywords “frailty”, “heart failure”, following the STROBE criteria and PRISMA recommendations. Outcomes. The first publication on frailty syndrome in patients with heart failure dates back to 2007, with research in this area peaking in 2021. The prevalence of frailty in heart failure varies due to differences in age groups, assessment methods, and study designs. Frailty affects approximately 70% of heart failure patients over 80 years of age, challenging the stereotype that frailty is solely associated with elderly individuals. Recently issued data by the World Health Organization (WHO) stated that although frailty and heart failure are common in older adults, the prevalence of frailty in this category of patients is independent of age. It is worth noting that frailty is more common in women, yet women tend to have a better prognosis. Diagnosing frailty in heart failure patients is challenging due to the overlap of clinical symptoms. The interaction between heart failure and frailty increases the risk of decompensation, dependency, and negative outcomes. Conclusions. Previous studies have primarily focused on frailty in elderly patients with heart failure. However, chronological age cannot represent an independent parameter in the assessment of frailty, and patients with heart failure should be assessed for the presence of frailty sovereignly of age for prudent risk stratification. Recognizing and early identification of frailty across all age groups will improve prognosis by reducing hospitalizations and enhancing quality of life.